ANALYSIS OF STUDENTS’ ERRORS AND WRITING FLOW IN NARRATIVE PARAGRAPH WRITTEN BY THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT THE UNIVERSITY OF MATARAM - Ramy Aisyah Fauzani; Lalu Thohir; Agus Saputra; Ahmad Zamzam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing narrative paragraphs poses challenges for EFL learners due to the demands of grammatical accuracy, coherence, and narrative flow. This study aims to analyze error types, identify their causes, and evaluate the writing flow in narrative paragraphs produced by first-semester English Education students at the University of Mataram, academic year 2024/2025. Employing a qualitative descriptive method, data were collected from 15 student writings and interviews with selected participants. The findings reveal that addition and misformation errors were the most frequent, followed by omission and misordering. The primary causes of errors stemmed from first language interference and direct translation, with carelessness contributing in some cases. In terms of writing flow, most students used transition signals and compound sentences effectively, yet struggled with proper comma usage. These results highlight the need for explicit instruction on narrative structure and focused feedback to enhance academic writing proficiency.